A researcher's guide to the National Statistics Socio-economic Classification - Rose, David, 1947 February 17-; Pevalin, David J. (London : SAGE, 2003)
Required reading for all users of government social classifications this volume evaluates how well the new system of socio-economic classification works in describing and explaining the relationships between social classes and key health and employment variables.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social classes -- Research -- Great Britain; Social classes -- Great Britain -- Statistics; Social classes -- Great Britain -- Classification